Silver Jubilee Souvenir 1976 - Planning Commission (Planning Commission, 1976)
The Central Statistical Organisation has many accomplishments to its credit during the 25years of its existence. The pace of progress should be further accelerated and the C.S.O. should be enabled to play a more effective role in standard setting and coordination. Even in the field of sample surveys where the National Sample Survey Organisation has the overall responsibility, C.S.O. should exercise vigilance in matters of standards and procedures to safeguard quality and comparability of data. Continued attention should be bestowed upon further refinements in definitions, imposition of checks at the design and analysis stages, prescription of formats for presentation of results and improvement of timeliness of official statistics. C.S.O. should be adequately equipped for this purpose and given the necessary technical expertise, official backing and support from the statistical elite.
Silver Jubilee Souvenir 1976
Central Statistical Organisation